URINARY TRACT INFECTION AMONG DIABETIC PATIENTS WITH REGARD TO THE RISK FACTORS, CAUSATIVE ORGANISMS AND THEIR ANTIMICROBIAL SUSCEPTIBILITY PROFILES: Life Science - Microbiology - ROHANI BORJ, MINA; TAGHIZADEHBOROJENI, SIMA; SHOKATI, AMENE; SANIKHANI, NAFISEH; POURGHADAMYARI, HOSSEIN; MOHAMMADI, ABBAS; ABBARIKI, EZZAT; GOLMOHAMMADI, TAGHI; MOJTABA HOSEINIHAROUNI, SEYED (International Journal of Life Science and Pharma Research, 2017)
Diabetes Mellitus(DM) is of the world’s biggest health problems .Human behavioral changes and lifestyle over the last century have resulted in a dramatic increase in incidences of diabetes worldwide. In the world, about420 million people have diabetes. This number is expected to double by 2025, disproportionately affecting working-age people. The present study was conducted to determine the risk factors, causative organisms and antimicrobial susceptibility of urinary tract infection (UTI) in diabetics and non-diabetics seeking treatment at ,Firoozgar hospital. Iran University of Medical Sciences, Tehran, Iran. This research designed based on a Prospective, descriptive and analytical study. Two hundreds samples:100 samples of urine and blood from diabetic subjects and 100 from control subjects were collected and urinalysis, culture and antimicrobial sensitivity done,during a period of 3 months (Jan 2015 to March 2015).Data obtained from urinalysis, culture and sensitivity was performed for detection of the infective etiology of UTI and antimicrobial susceptibility,to determine prevalence of UTI among both groups. Prevalence of UTI in diabetics was 32.0% and in non-diabetics 22.0% (P=0.111). The most commonly isolated pathogens for both groups were E. coli (48.1%), Enterobacter (24.1%), Klebsiella spp (13%), Candida albicans (9.3%), and S. aureus (3.7%).Isolates in both groups had similar antibiotic sensitivity patterns. The present study identified older age, female gender, hyperglycemia, elevated HbA1c, glycosuria, albuminuria as risk factors of UTI in diabetics. Aminoglycosides, nitrofurantoin,gatifloxacin had excellent activity against the isolates, and could be used for empirical treatment.